Station eleven [videorecording (DVD)] - Somerville, Patrick, 1979- (Paramount, 2023)
A post-apocalyptic saga spanning multiple timelines, this limited drama series tells the stories of survivors of the devastating flu as they attempt to rebuild and reimagine the world anew while holding on to the best of what's been lost.